Modified PPIs (a search for the better) - Hussein Abdel-Hamid (Wolters Kluwer Medknow Publications, 2016)
'Modified PPIs' is the term given to proton pump inhibitors (PPIs) introduced after the four conventional PPIs - omeprazole, lansoprazole, pantoprazole, and rabeprazole - all of which have similar actions and limitations and are produced by similar technologies. Modified PPIs include isomeric PPIs, dual delayed release PPIs, immediate release PPIs, and long half-life PPIs, which are manufactured by different technologies to overcome certain limitations of conventional PPIs. This modified category includes esomeprazole (Nexium), dexlansoprazol (Dexilent), omeprazole-sodium bicarbonate mixture (Zegred), and S.tenatoprazole. Although some of these new products have better efficacy, longer duration of action, can be taken with disregard to meals, and have better nocturnal effect, we still lack the ideal PPI.